2021
DOI: 10.34172/ajcmi.2021.11
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Prevalence and Antibiotic Resistance in Vancomycin-Resistant Enterococcus from Clinical Samples – Demographics and Phenotypes

Abstract: Background: Of all enterococci species, the most renowned clinically as multidrug-resistant pathogens are Enterococcus faecium and Enterococcus faecalis. Vancomycin-resistant Enterococcus (VRE) species are the principal cause of opportunistic hospital-acquired infections, due to numerous resistance mechanisms. Methods: In this study, the prevalence and antibiotic resistance profiles of VRE according to clinical sources from three selected hospitals in Southwest-Nigeria were investigated. Altogether, 431 sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…In this study, the vanA and vanB genes screened conforms to other studies where vanA genes were detected and vanB gene was not detected (Adegoke et al, 2022). This disagrees with other studies that reported the absence of vanA genes (Adeyemi et al, 2021). Reportedly, vanA gene has been the most common vancomycin resistance gene (Igbinosa and Beshiru, 2019a).…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…In this study, the vanA and vanB genes screened conforms to other studies where vanA genes were detected and vanB gene was not detected (Adegoke et al, 2022). This disagrees with other studies that reported the absence of vanA genes (Adeyemi et al, 2021). Reportedly, vanA gene has been the most common vancomycin resistance gene (Igbinosa and Beshiru, 2019a).…”
Section: Discussioncontrasting
confidence: 61%
“…The detection of phenotypic virulence factors have also been reported (Igbinosa and Beshiru, 2019). These virulence determinants including hemolysin and gelatinase aid nutrient acquisition from host tissues and advance invasion, thereby increasing the severity of human infections (Adeyemi et al, 2021). Biofilm formation aids disease development as it boosts the persistence of infections and reduces antimicrobial activity (Igbinosa et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation